Assessment of Deoxyribonuclease Activity in Serum Samples of Patients With Systemic Lupus Erythematosus: Fluorescence‐Based Method Versus ELISA. Issue 6 (18th April 2016) - Vancevska, Aleksandra; Nikolic, Aleksandra; Bonaci‐Nikolic, Branka; Skiljevic, Dusan; Radojkovic, Dragica
Abstract : Background: We report the improvement of previously described method for determining deoxyribonuclease (DNase) activity in serum samples that uses a fluorescently labeled DNA fragment as a substrate Methods: Activity of serum DNase was analyzed in 31 patients with systemic lupus erythematosus (SLE) and 13 healthy individuals by fluoresence‐based method and ELISA test Results: We found a mean decrease in DNase activity between cases and controls of 12.46% measured by the fluoresence‐based method and of 12.21% measured by ELISA method. High level of positive correlation between two methods for DNase activity was observed: P < 0.001 and Pearson correlation coefficient 0.740. Decreased DNase activity was found in 25 of 31 SLE patients (81%) by fluoresence‐based method and in 24 of 31 SLE patients (77%) by ELISA test. We also observed the significant positive correlation between titer of anti‐dsDNA antibodies and DNase activity measured by both methods ( P < 0.05). Conclusions: The key improvement is the use of internal control in the fluorescence‐based method, which diminishes the influence of technical errors on the obtained results and increases reliability of the assay. This improved fluorescence‐based method, with additional validation, may provide an alternative to more expensive and time‐consuming conventional methods, such as ELISA.